How accelerating the electrification of the van sector in Great Britain can deliver faster CO2 and NOx reductions. (January 2023) - Yang, Zhuoqian; Tate, James; Morganti, Eleonora; Philips, Ian; Shepherd, Simon
Highlights: CO2 and NOx emission trends from the van sector in Great Britain are investigated. Scenarios designed based on phasing out internal combustion engine vans by 2030. The tailpipe net-zero target will be reached by 2050 under all scenarios. A rapid transition to electric vans could achieve a substantial emission reduction. Abstract: As a major emission contributor with significant growth potential, the light goods vehicles (vans) play an important part in achieving net-zero. In 2020 the UK government committed to phasing out sales of new internal combustion engine (ICE) vans by 2030, but the impact of the policy and how far are we to decarbonize the entire van fleet by 2050 is unclear. This paper investigates the CO2 and NOx emission trends in the van sector in Great Britain under the 2030 ICE phase-out. ECCo model 1 is used to forecast the future van population by powertrain. The annual van mileage is estimated based on the van activity survey 2 . The instantaneous emission model PHEM, NAEI emissions inventory and remote sensing measurements are used to parameterize real-world driving emission factors of CO2 and NOx . Scenarios have been set out to assess the impact of enablers and barriers affecting the pace of emission reductions. Results suggest vans are on track to reach the tailpipe net-zero target by 2050 under all scenarios, and the speed of NOx reduction is even faster. A rapid transition to battery electric vans in the early to mid-2020s will significantly lower CO2, with associated estimated monetary benefits of £1.3 billion.